PENGAKUAN DAN PENGESAHAN ANAK LUAR KAWIN DARI PASANGAN SUAMI ISTRI YANG BERBEDA KEWARGANEGARAAN (STUDI PENETAPAN PENGADILAN NEGERI BATAM NO. 79/ PDT.P/ 2014/ PN.BTM) - NEW YEARLINA S (PREMISE LAW JURNAL, 2017)
ABSTRACT The openness of Indonesia for international activities and association has brought certain impacts on social relationship in term of family relationship, particularly on marriage. Batam lies on a strategic location in the international shipping passageway. It has caused quite many mixed marriages in its society. The presence of a child in a mixed marriage has a significant meaning. In reality, the presence of a child in a marriage does not necessarily mean happiness. It usually happens to an illegitimate child. He/she needs to be recognized by his/her parents regarding all consequences in inheritance, citizenship, custody, and so on. Recognition does not directly turn an illegitimate child into a legitimate one. He/she becomes a legitimate child when his/her parents solemnize their marriage. Keywords: Recognition, Validation, an Illegitimate Child from a Husband and Wife with Different Citizenships